Desain Pengembangan Kurikulum Model Ralph Tyler pada Pembelajaran Al-Qur’an Hadits di Tingkat Madrasah Ibtidaiyah - Malia Fransisca; Muhammad Bintang Fadhlurrahman; Farah Edhar Khaerunisa; Nova Nurfani; Trisna Nurfadilah (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2021)
Improvements in education and curriculum must be carried out in line with the development of science. It is done to create a proper and correct education system. Frequent changes in educational curricula present some problems. The education curriculum in Indonesia has undergone twelve changes but is still experiencing problems that tend to be the same as those faced by previous curricula. The purpose of this study is to offer a model of Ralph Tyler's curriculum development and its implications for learning the Al-Qur’an Hadith at the elementary school level. The research method used in this study is qualitative methods. Researchers look for references in various mass media to clarify the information in this study. This type of research is a literature study, so it attaches great importance to information and clarity from the mass media in developing and identifying the case. Tyler's curriculum development model has several advantages and disadvantages. Elementary school is one level of education unit that can describe and identify how Tyler's curriculum can develop, especially in learning the Al-Qur’an and Hadith. Tyler's curriculum describes how a student gains experience during learning activities. Learning Al-Qur’an Hadith must have clear goals and provide useful learning experiences for students. The results of this study indicate that there are four forms of curriculum design for Al-Qur’an Hadith learning. First, it must determine the expected educational goals or outputs. Second, it determines the learning experience. Third, it organizes the learning experience. Fourth, it evaluates the effectiveness of the learning experience.